Role of glycoprotein Ibα mobility in platelet function - van der Wal, Dianne E.; Verhoef, Sandra; Schutgens, Roger E. G.; Peters, Marjolein; Wu, Yaping; Akkerman, Jan Willem N. (Thrombosis and Haemostasis, 2010)
Incubation at 0°C is known to expose β-N-acetyl-D-glucosamine residues on glycoprotein (GP) Ibα inducing receptor clustering and αMβ2-mediated platelet destruction by macrophages. Here we show that incubation at 0/37°C (4 hours at 0°C, followed by 1 hour at 37°C to mimic cold-storage and post-transfusion conditions) triggers a conformational change in the N-terminal flank (NTF, amino acids, aa 1–35) but not in aa 36–282 of GPIbα as detected by antibody binding. Addition of the sugar N-acetyl-D-glucosamine (GN) inhibits responses induced by 0/37°C. Incubation at 0°C shifts GPIbα from the membrane skeleton to the cytoskeleton. Different GPIbα conformations have little effect on VWF/ristocetin-induced aggregation, but arrest of NTF change by GN interferes with agglutination and spreading on a VWF-coated surface under flow. Strikingly, incubation at 0/37°C initiates thromboxane A2 formation through a von Willebrand factor (VWF)-independent and GPIbα-dependent mechanism, as confirmed in VWF- and GPIbαﺹdeficient platelets. We conclude that the NTF change induced by 0/37°C incubation reflects clustering of GPIbα supports VWF/ristocetin-induced agglutination and spreading and is sufficient to initiate platelet activation in the absence of VWF.
Keywords: Glycoprotein Ibα; cold-storage; cytoskeleton; platelet; thromboxane A2